EVALUASI EFEKTIVITAS PELAKSANAAN PEMILIHAN KEPALA DESA (PILKADES) SERENTAK DI KABUPATEN PAMEKASAN TAHUN 2015 - Imam, Achmad; Ma'mun, Sukron (Universitas Madura, 2017)
This research is motivated by the implementation of the village elections simultaneously in Pamekasan is one indicator of the development of democracy in Pamekasan. Action required evaluation of the implementation of village elections simultaneously in Pamekasan for the implementation of village elections simultaneously in Pamekasan which will be held later to run well. By adhering to the theory put forward by Solichin Abdul Wahab as described in the literature review, then parameters or benchmarks on the effectiveness of a program or activity can be measured by the equation= So, the implementation of village elections simultaneously in Pamekasan 2015 can be said to be run effectively if results achieved from the implementation of village elections simultaneously in Pamekasan in 2015, proportional or appropriate to the objectives of the village elections simultaneously in Pamekasan 2015 . the method used is a qualitative descriptive so that the data is displayed in the form of data from interviews and documentation of results. Analysis of data using Domain analysis technique that aims to know in general about the implementation of village elections simultaneously in Pamekasan 2015 (a study on the evaluation of the effectiveness of the implementation of village elections in rural districts Murtajih Pademawu Pamekasan 2015). The results of his research, found their effectiveness in the implementation of village elections simultaneously in Pamekasan with the findings of the results achieved from the aim of implementing village elections simultaneously itself, which to streamline costs in the implementation of the elections and simultaneously in 2015 issued by the government, to reduce the acts of fraud such as money politics in the elections and simultaneous implementation by 2015 and to reduce the amount of gambling that is done by the people of the village and outside the village in the elections and the simultaneous implementation in 2015.